COVID-19: A new challenge for mental health and policymaking recommendations - Musaad A. Alshammari; Tahani K. Alshammari (Elsevier, 2021)
The coronavirus disease 2019 (COVID-19) infection has emerged lately, leading to a serious public health threat. The clinical features associated with COVID-19 are yet to be conclusively documented. Caution is needed when interpreting the severity of the symptoms as most of the diagnosed patients are those attending clinical assessments. Features of COVID-19 are far from understood. There is a suggested increased risk of COVID-19 infection among people with mental health disorders, which is primarily attributable to the challenges associated with limited resources. There are a variety of reasons why individuals with mental health disorders are more susceptible to infectious diseases. There is currently no specific recommended antiviral treatment. The interventions now used are supportive treatments to alleviate the symptoms and invasive mechanical ventilation. In this review, we discuss the adverse events associated with COVID-19 vaccinations. We further highlight the need to develop guidelines and recommendations for managing patients with mental health. It is evident from this review, there is a need to provide training programs with interprofessional, multidisciplinary communication channels.